Does Job Search Assistance Really Raise Employment? - Lionel Cottier; Yves Flückiger; Pierre Kempeneers; Rafael Lalive (Institute of Labor Economics (IZA), 2018)
We study how job search assistance (JSA) affects employment in a randomized pilot study with long run administrative data. JSA increases employment in the first year after assignment. In the second year, when most job seekers have left JSA, the employment gains evaporate, and even turn into losses in the third year. This sinusoidal pattern is consistent with job finding and employment loss transitions. Job seekers assigned to JSA find employment faster but, once employed, also lose employment faster, especially once eligible for new unemployment benefits. Job seekers assigned to JSA have similar types of contracts and re-employment earnings, but somewhat worse positions in the firm and are more likely to have a part time job.
Keywords: J64; J68; 330; job placement; long term unemployment; job loss; job search assistance; active labor market policy